Tuberculous otomastoiditis: analysis of otological tuberculosis with intact tympanic membrane - Gupta, Nandini; Sharma, Divyanshu; Parikh, Darshan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
In recent years extra pulmonary tuberculosis has more frequently been associated with mastoiditis in patients with immunodeficiency state. Although tuberculosis of the mastoid or otomastoiditis is a very rare complication of tuberculosis today, when occurs it may cause significant morbidity. Complications such as facial paralysis and permanent hearing loss may develop. Our purpose was to evaluate the differential findings of tuberculous otomastoiditis and evaluation of outcomes in patients undergoing surgery along with anti-tubercular therapy rather than patients receiving only anti-tubercular therapy. We reviewed 12 cases of TOM, all of which had been confirmed on sputum and pathological examination following middle ear mucosal biopsy. Neuroradiologists analyzed the typical findings of HRCT temporal bone. Tympanomastoid ear surgery was planned according to the extent of the disease involved. The soft tissue attenuation in the entire middle ear cavity and extension to the external auditory canal (EAC) or mucosal thickening of the bony EAC, erosion of the ossicles and scutum was clinically significant. Patients who underwent tympanomastoid surgery showed better prognosis than the patients receiving anti tubercular drugs alone. Patients with extra-pulmonary tuberculosis, especially otomastoiditis should get operated to remove the disease along with anti-tubercular treatment to prevent complications.